Interactions of OxyR with the promoter region of the oxyR and ahpC genes from Mycobacterium leprae and Mycobacterium tuberculosis. - Dhandayuthapani, S (1997)
In contrast to the intact oxyR gene (a homolog of the central regulator of peroxide stress response in enteric bacteria) in Mycobacterium leprae, this gene is inactive in all strains of M. tuberculosis. In both species, oxyR is divergently transcribed from ahpC, which encodes a homolog of alkyl hydroperoxide reductase. To initiate investigations of the regulation of oxidative stress in mycobacteria and consequences of the elimination of oxyR in M. tuberculosis, in this work we tested the hypothesis that mycobacterial OxyR acts as a DNA binding protein and analyzed its interactions with the oxyR and ahpC promoters. M. leprae OxyR was overproduced and purified, and its binding to the oxyR-ahpC intergenic region of M. leprae was demonstrated. By using a sequential series of overlapping DNA fragments, the minimal OxyR binding site was delimited to a 30-bp DNA segment which included a palindromic sequence conforming with the established rules for the LysR family of regulators. A consensus sequence for the mycobacterial OxyR recognition site (cTTATCggc-N3-gccGATAAg) was deduced based on its conservation in different mycobacteria. A variance in two potentially critical nucleotides within this site was observed in M. tuberculosis, in keeping with its reduced affinity for OxyR. Transcription of plasmid-borne M. leprae oxyR and ahpC was investigated in M. smegmatis and M. bovis BCG by S1 nuclease protection and transcriptional fusion analyses. Two mRNA 5' ends were detected in each direction: (i) P1oxyR and P2oxyR and (ii) P1ahpC and P2ahpC. The binding site for OxyR overlapped P1oxyR, reminiscent of the autoregulatory loops controlling expression of oxyR in enteric bacteria and characteristic of the LysR superfamily in general. This site was also centered 65 bp upstream of P1ahpC, matching the usual position of LysR-type recognition sequences in relationship to positively controlled promoters. Superimposed on these features was the less orthodox presence of multiple transcripts and their unique arrangement, including a region of complementarity at the 5' ends of the P2ahpC and P2oxyR mRNAs, suggesting the existence of complex regulatory relationships controlling oxyR and ahpC expression in mycobacteria.